Unbalanced between Work Ethic and Result of Poor Families in Alue Naga Community - Sa'i (Jurnal Intervensi Sosial, 2023)
Abstract Work Ethic is one of the important keys to get maximum results. In Aceh there is a pearl of wisdom about work ethic: Menyoe hana tausaha pane atra roet di manyang (if we do not work, there won’t be treasures falling from the sky). Poverty is not without causes; among the causes is work ethic. This paper looks at the work ethic of families in Gampong Alue Naga, especially the youth, because they are the most potential members of society. The study used qualitative design with descriptive analysis. Data was obtained through observation, interviews and documentation. The results showed that the family work ethic in Alue Naga was considered very good, however, they still lived poor lives. Based on the study, there were some factors affecting their work results, such as: narrow employment opportunities; their work as fishermen was still using traditional method, their equipment for work such as boats, trawls; fishing rods were still very limited in numbers and their work was also not supported by sufficient skills. Therefore, despite the high work ethic, the majority of people in this Gampong (village) were still poor. It proved that work ethic alone is not enough to gain a better income. It is highly suggested that the government and related parties who feel compelled to advance society in the economic field need to provide guidance, direction and assistance to residents who are still eager to work in order to increase their incomes. Keywords: Work Ethic; Poor Families; Families Economy